2021
DOI: 10.3390/ani11082314
|View full text |Cite
|
Sign up to set email alerts
|

Introducing the World’s First Global Producer Price Indices for Beef Cattle and Sheep

Abstract: While international beef and sheep meat price developments are usually measured with meat trade prices (provided by FAO), no comparable information exists on world average of national prices that producers receive for livestock. This paper aims to fill this gap by introducing a set of global producer price indices representing cattle, lambs, and sheep prices as received by producers: the agri benchmark of weaner cattle, finished cattle, lambs and lambs and sheep price indices. These Laspeyres, production-weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Studies conducted in South America showed that the pandemic has exacerbated for meat producers their already existing problems, stemming from political instability, weak economic growth, low consumer purchasing power, high inflation rate and rapid currency depreciation (Almadani et al, 2021). The decrease in demand for meat and meat products was also contributed to by the media, which highlighted the zoonotic source of SARS-CoV-2, and thereby the question of the safety of consuming meat (Attwood and Hajat, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies conducted in South America showed that the pandemic has exacerbated for meat producers their already existing problems, stemming from political instability, weak economic growth, low consumer purchasing power, high inflation rate and rapid currency depreciation (Almadani et al, 2021). The decrease in demand for meat and meat products was also contributed to by the media, which highlighted the zoonotic source of SARS-CoV-2, and thereby the question of the safety of consuming meat (Attwood and Hajat, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Owing to calculation error, the Chain Laspeyres index is more accurate in reflecting the trend of price changes. It is a commonly used method in statistical offices in national and international organizations worldwide, such as the FAO and the National Institute of Statistics and Economic Studies in France (INSEE) [18].…”
Section: Wireless Communications and Mobile Computingmentioning
confidence: 99%